Desvelando conexões entre docência na EaD e a dromoaptidão cibercultural : o caso do Instituto Federal de Alagoas - Soeira, Elaine dos Reis (2020)
This thesis developed in the scope of the Postgraduate Program in Education (PPGED), of the Federal University of Sergipe (UFS), concentration area Education, Communication and Diversity, Education and Communication line, had as object of study the relationship between identity professional in distance learning and the level of cybercultural dromoaptitude of students. The objectives outlined for research were: to investigate the relationship between professional identity and the level of cybercultural dromoaptitude, in the pedagogical teaching practices in distance education at IFAL, from the representations of students, tutors and teachers of undergraduate courses, as a general objective; identify the profile of students, tutors and professors of undergraduate courses offered in distance education, in relation to cybercultural dromoaptitude and cybercultural skills; recognize structural elements that support the social representations of professionals and students about teaching in distance education; to analyze how the relationship between teaching in DE is constituted and the level of cybercultural dromoaptitude of students, as specific objectives. This was a case study, carried out at the Federal Institute of Alagoas, specifically in undergraduate courses in Letters/Portuguese and Biological Sciences, offered at a distance, with students, tutors and professors linked to these courses participating in the research. 37 (thirty-seven) students participated in the research, linked to the Cajueiro, Arapiraca, Maragogi, Palmeira dos Índios, Maceió, São José da Laje and Penedo hubs. Considering the group of professionals, there were 19 (nineteen) participants, 14 (fourteen) acting as tutors and 6 (six) acting as training teachers. The research was qualitative, exploratory-descriptive, with phenomenological inspiration and structured from the theoretical-methodological framework of the societal approach of Social Representations. Data collection took place through an online questionnaire and data analysis was performed with the support of the software IRAMUTEQ and SPSS. Theoretically, the research was based on the following concepts: teaching; teaching in distance education; professional identity; learning in distance education; dromocracy and cybercultural dromoaptitude. The investigation made it possible to draw a cybercultural profile of the professionals and students participating in the research, identifying the level of dromoaptitude in which they find themselves. In addition, it was possible to reflect on the teaching-learning process in distance education at the institution, discuss teaching and professional identity based on the professionals' representations and relate professional identity and cybercultural dromoaptitude. The research question “how is the relationship between the professional teaching identity in distance education based on the level of cybercultural dromoaptitude of students” was answered from the analysis of the representations of students and teachers about the cybercultural profile, the teaching- learning and teaching, making it clear that the level of development of cybercultural dromoaptitude of students implies redefining the identity of professionals working in distance education, especially in the case of tutors, as the specificities and demands of students' learning require more in-depth interventions, with the proposition of learning situations, going beyond the limits of mere advice to teachers.